A companion to Rainer Werner Fassbinder - Peucker, Brigitte (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2012)
This is the first of its kind to engage with this important figure. Essays by an international group of scholars consider this controversial director's contribution to German cinema, German history, gender studies, and auteurship. - A fresh collection of original research providing diverse perspectives on Fassbinder's work in films, television, poetry, and underground theatre. - Rainer Werner Fassbinder remains the preeminent filmmaker of the New German Cinema whose brief but prolific body of work spans from the latter half of the 1960s to the artist's death in 1982. - Interrogates Fassbinder's influence on the seminal ideas of his time: auteurship, identity, race, queer studies, and the cataclysmic events of German twentieth century history - Contributions from internationally diverse scholars specializing in film, culture, and German studies. - Includes coverage of his key films including: Gods of the Plague (1970), Beware of a Holy Whore (1971), The Bitter Tears of Petra von Kant (1972), Martha (1973) (TV), World on a Wire (1973), Effi Briest (1974), Ali: Fear Eats the Soul (1974), Fox and His Friends (1975), Fear of Fear (1975), Chinese Roulette (1976), In a Year With 13 Moons (1978), Despair (1978), The Third Generation (1979), Berlin Alexanderplatz (1980) (TV), and Querelle (1982).
Introduction / Brigitte Peucker -- Life and Work. The Other Planet Fassbinder / Juliane Lorenz -- R.W. Fassbinder: Prodigal Son, Not Reconciled? / Thomas Elsaesser -- Rainer "Maria" Fassbinder: Cinema between Literature and Life / Leo A. Lensing -- Fassbinder Scenes / Wayne Koestenbaum -- Genre-Influence-Aesthetics. Imitation, Seriality, Cinema: Early Fassbinder and Godard / Laura McMahon -- Exposed Bodies-Evacuated Identities / Claire Kaiser -- Redressing the Inaccessible through the Re-Inscribed Body: In a Year with 13 Moons and Almodovar's Bad education / Victor Fan -- Nudity and the Question: Chinese Roulette / Eugenie Brinkema -- Color, Melodrama, and the Problem of Interiority / Brian Price -- Fassbinder's Work : Style, Sirk, and Queer Labor / John David Rhodes -- A Nagging Physical Discomfort: Fassbinder and Martha / Joe McElhaney -- Beyond the Woman's Film: Reflecting Difference in the Fassbinder Melodrama / Nadine Schwakopf -- Through the Looking Glass: Fassbinder's World on a Wire / Brad Prager -- Other Texts-Other Media. Violently Oscillating: Science, Repetition, and Affective Transmutation in Fassbinder's Berlin Alexanderplatz / Elena del Rio -- In Despair : Performance, Citation, Identity / Brigitte Peucker -- Declined Invitations: Repetition in Fassbinder's Queer "Monomusical" / Caryl Flinn -- Fassbinder's France: Genet's Mise-en-Scene in Fassbinder's Films / Olga Solovieva -- Un-framing the Image: theatricality and the Art World of Bitter Tears / Brigitte Peucker -- A Novel Film: Fassbinder's Fontane Effi Briest / Elke Siegel -- Swearing and Forswearing Fidelity in Fassbinder's Berlin Alexanderplatz / Paul Coates -- History-Ideology-Politics -- "There are many ways to fight a battle": Young Fassbinder and the Myths of 1968 / Eric Rentschler -- A Generation Later and Still Unrepresentable? Fassbinder and the Red Army Fraction / Frances Guerin -- Two Kinds of Excess: Fassbinder and Veit Harlan / Laura J. Heins -- Jolie Laide: Fassbinder, Anti-Semitism, and the Jewish Image / Rosalind Galt -- Impossible, Impolitic: Ali: Fear Eats the Soul and Fassbinder's Asynchronous Bodies / Elena Gorfinkel -- "So Much Tenderness": Rainer Werner Fassbinder, Gunther Kaufmann, and the Ambivalences of Interracial Desire / Tobias Nagl and Janelle Blankenship -- Rainer, Rosa, and Werner: New Gay Film as Counter-Public / Randall Halle -- Fassbinder's Fox and His Friends and Gay Politics in the 1970s / Ronald Gregg -- Querelle is Finality / Roy Grundmann.
Includes bibliographical references and index.
Print version record.
Keywords: Fassbinder, Rainer Werner, -- 1945-1982 -- Criticism and interpretation; Fassbinder, Rainer Werner, -- 1945-1982; Ebooks -- UML; PERFORMING ARTS -- Film & Video -- Direction & Production; Performing Arts; Electronic books; Criticism, interpretation, etc